Genetic analysis of a Bison bison herd derived from the Yellowstone National Park population. Issue 6 (1st December 2014) - Herman, Julia A.; Piaggio, Antoinette J.; Halbert, Natalie D.; Rhyan, Jack C.; Salman, M. D.
Abstract : The objective of this study is to inventory the current genetic diversity of the bison quarantine feasibility study (BQFS) herd originating from Yellowstone National Park (YNP) using previously described microsatellite, mitochondrial and nuclear DNA markers with the aim to determine the degree, if any, of cattle DNA introgression in this herd. This work can provide an important tool in monitoring and managing bison genetic diversity as brucellosis‐free reintroduced herds are re‐established throughout the US for conservation purposes. The BQFS composed of 89 Bison bison from YNP that were quarantined and tested to qualify as free of brucellosis in 2006–2007. Understanding genetic diversity of the herd is important to determine if any genetic characteristics such as cattle DNA introgression or low genetic diversity may threaten the herd's protected status. We evaluated genetic diversity at 42 microsatellite loci representing each of the nuclear chromosomes in the bison genome. We found no detectable evidence of cattle DNA introgression in this herd through nuclear markers and mitochondrial DNA analysis. Parentage analysis of the BQFS herd indicated that the majority of mature adults were actively breeding and contributing offspring. Genetic diversity levels in the quarantined herd were high and comparable to the YNP parent herd, suggesting a low risk of genetic loss in the near future. Based on these findings, the genetic diversity currently available within the BQFS herd will provide a strong foundation for bison reintroduced herds and for the preservation of the species.